2018
DOI: 10.1007/s12040-018-1003-7
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between felsic granitoids and mafic dykes in Bundelkhand Craton: A field, petrographic and crystal size distribution study

Abstract: In Bundelkhand Craton of central India, mafic dykes intruded when granitoids was partly crystallized. Cuspate-lobate boundary along the contact of granitoids and mafic magma indicates magma mingling in outcrop scale while textural evidence of mingling is represented by acicular apatite morphologies, titaniteplagioclase ocelli and ophitic-subophitic texture, mafic clots, resorbed plagioclase, and hornblende-zircon associations. Mingling also caused thermal exchange and fluid activity along the boundary between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 54 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Presence of plagioclase crystals across the contact boundary is one of the most common evidence of mixing reported by Ramiz and Mondal (2017). Deb and Bhattacharya (2018) suggested that chemical analysis should also be supported by meso-and microscale textural evidences to confirm the signature of magma mixing. They reported acicular apatite, titanite-plagioclase ocelli, ophiticsubophitic texture, mafic clots, resorbed plagioclase, hornblendezircon asscociation and cuspate-lobate boundary along the contact of granitoid and mafic magma which confirm the magmatic mixing in the BuC.…”
Section: Geodynamic Evolution In Space and Timementioning
confidence: 85%
“…Presence of plagioclase crystals across the contact boundary is one of the most common evidence of mixing reported by Ramiz and Mondal (2017). Deb and Bhattacharya (2018) suggested that chemical analysis should also be supported by meso-and microscale textural evidences to confirm the signature of magma mixing. They reported acicular apatite, titanite-plagioclase ocelli, ophiticsubophitic texture, mafic clots, resorbed plagioclase, hornblendezircon asscociation and cuspate-lobate boundary along the contact of granitoid and mafic magma which confirm the magmatic mixing in the BuC.…”
Section: Geodynamic Evolution In Space and Timementioning
confidence: 85%